THE INFLUENCE OF LEARNING ENGLISH ON PERSONAL WORLDVIEW AND STATEMENTS - Rasuljonov Bekhruzbek Ravshanjon ugli (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract. This article discusses how a person’s worldview, beliefs, thinking, and even lifestyle can change through learning foreign languages, the main factors causing this, as well as the negative and positive aspects affecting society. The article analyzes the system for assessing the level of a foreign language based on world standards, as well as the degree to which the learner’s knowledge, skills, and socio- psychological state change at each stage.